PENERAPAN METODE ROLE PLAYING DALAM PEMBELAJARAN DRAMA UNTUK PENINGKATAN KEMAMPUAN BERBICARA - Suhandi, Ya’ Dedi (Universitas Tanjungpura, 2018)
The purpose of this study as follows. First, it reviews the application of the role playing method in the learning drama to know the learning processquality, especially the students’ attitude, namely interest, activity, responsibility, courage, and enthusiastic. Second, it reviews the application of the role playing method in the learningdrama to know the quality of students’ speaking, especially pronunciation, intonation, fluency, expression, and comprehension.Actionis implemented during three cycles. The examined data is the learning process, especially the students’ attitude and speaking. The data source is the fifth grade teacher through the lesson plans, score list of students’ attitude, score list of the students’ speaking ability, teacher’s activity by using an indirect technique, namely observation and documentation.Based on theresearch results, it is concluded that role playing method can improve the quality of the learning process, especially the students’s attitude and speaking. This can be evidenced by the increased percentage as follows. First, students’ attitude on aspects of interest, activity, responsibility, courage, and enthusiastic in the cycle I, II, and III. Second, the quality of students’ speaking ability evidenced by the average score in the first cycle is 70 and 48% levels of completeness. In the second cycle, ithappened increasing to 79 with a 74% level of completeness. In the third cycle, ithappened a significant increasing, namely 87 to 93% levels of completeness.